2021
DOI: 10.1016/j.jrp.2021.104092
|View full text |Cite
|
Sign up to set email alerts
|

Do voices carry valid information about a speaker’s personality?

Abstract: Author contributions: CS came up with the study idea, JS, CS, and RCA contributed to the study design. All authors performed data collection. RCA wrote the analysis plan for which JS simulated data. CS and DF performed the voice analyses, based on scripts by DAP and DF. JS cleaned the data. RCA analyzed the data, created the codebook for all variables and the supplementary website. JS drafted the Stage 1 and the Stage 2 manuscript, RCA helped with the statistical analyses and advised the results part. All auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 86 publications
5
12
0
Order By: Relevance
“…In many instances, the direction of the voice-personality correlations was in line with previous research. For instance, Agreeableness was negatively correlated with pitch variation (similar to Mairesse et al, 2007), Openness to Experience was negatively correlated with pitch (Stern et al, 2021), Extraversion was positively correlated with speech rate (Borkenau & Liebler, 1992), and intensity (Mairesse et al, 2007), but neither of those correlations reached statistical significance. Some other correlations were more complicated.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In many instances, the direction of the voice-personality correlations was in line with previous research. For instance, Agreeableness was negatively correlated with pitch variation (similar to Mairesse et al, 2007), Openness to Experience was negatively correlated with pitch (Stern et al, 2021), Extraversion was positively correlated with speech rate (Borkenau & Liebler, 1992), and intensity (Mairesse et al, 2007), but neither of those correlations reached statistical significance. Some other correlations were more complicated.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies that have tested the relations between voice and personality have mainly focused on five voice features: pitch, which is the perceived "highness" or "lowness" of voice; pitch variation, which refers to the fluctuation (standard deviation) of pitch; voice intensity, which is the perceived "loudness" in voice; intensity variation, which is the standard deviation of voice intensity; and speech rate, defined as the number of words per second, indicating how fast someone speaks. In the past 30 yearssince the introduction of objective voice analysis softwarethe number of studies that have explored the relation between voice and self-reported personality has been limited, and the main findings suggest that Openness to Experience is negatively correlated with voice intensity (Borkenau & Liebler, 1992) and pitch (Stern et al, 2021); Conscientiousness is negatively correlated with pitch and voice intensity (Batrinca et al, 2011); Extraversion is positively correlated with voice intensity and speech rate (Borkenau & Liebler, 1992;Mairesse et al, 2007), and negatively correlated with intensity variation (Mairesse et al, 2007) and pitch (Stern et al, 2021); Agreeableness is negatively correlated with pitch variation (Mairesse et al, 2007); and Emotional Stability is negatively correlated with pitch (Stern et al, 2021).…”
mentioning
confidence: 99%
“…Longer utterances are likely to convey more information than shorter utterances regarding not only the nonverbal parameters of the vocalizer's voice but also their prosody or the vocalizer's way of speaking, which might be perceptually related to personality (Zellner Keller, 2005). Indeed, voice pitch only partly explains the personality judgements of unseen vocalizers (Stern et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds if not thousands of experimental studies have shown that the human voice plays a central role in predicting listeners' perceptions of the social and biological qualities of vocalizers, including psychological and physical traits (reviewed in: Aung & Puts, 2020;Kamiloğlu & Sauter, 2021;Kreiman & Sidtis, 2011;Pisanski & Bryant, 2019). For example, the nonverbal properties of a person's voice, particularly fundamental frequency (f o ) perceived as voice pitch, and formant frequencies affecting voice timbre, can predict listeners' judgments of a vocalizer's personality traits (Stern et al, 2021), social dominance (Aung & Puts, 2020;Borkowska & Pawlowski, 2011;David A. Puts et al, 2016), attractiveness (reviewed in Pisanski & Feinberg, 2019), and health (Vukovic et al, 2010), to name only a few.…”
Section: Introductionmentioning
confidence: 99%
“…The pitch of voice is inversely correlated with perceived dominance; the lower the voice pitch, the greater the perceived dominance (Puts et al, 2006 ). Adjusted for the effects of sex and age, Stern et al ( 2021 ) found that participants with lower voice pitch self-report as lower on neuroticism, but higher on dominance, extraversion, and openness to experience, as well as more unrestricted on sociosexual orientation, sociosexual behavior, sociosexual attitudes, and sociosexual desire. Paralinguistic intonational meanings have been argued to be grounded in terms of the Frequency Code (Ohala, 1983 , 1984 ; Chen et al, 2004a ), which exploits the link between larynx size and vibration rates of the vocal cords for the expression of power relations, and the Effort Code (Gussenhoven, 2002 ), which refers to the positive correlation between articulatory efforts and articulatory precision (de Jong, 1995 ).…”
Section: Introductionmentioning
confidence: 99%